Phylogenetic relationship between species of genus Cattleya as a function of crossing compatibility - Stort, MNS (Revista de Biologia Tropical, 1984)
The applicability of the gradcd fertility method in the study of the phylogenctic distance of orchids was investigated with emphasis on the production of F1 hybrid secds with cmbryos. Specics of the genus Cattleya, subgenera Monophyllae, Aurantiacae and Cattleya wece used and the results compared with those obtained with morphological and chemical methods.

La aplicabilidad del grado de fertilidad graduada en el estudio de la distancia filogenética de las orquídeas fue investigada a través de la producción de semillas híbridas F 1 con embrión. Fueron usadas especies del género Catlleya, y de los sub-géneros Monophyllae, Aurantiacea y Cattleya. Nuestros resultados fueron comparados con aquellos obtenidos a través de métodos morfológicos y particularmente por medios estadísticos y cromatográficos usados por otros autores.